Cities of Entanglements Social Life in Johannesburg and Maputo Through Ethnographic Comparison - Heer, Barbara (Urban Studies, 2019)
How do people live together in cities shaped by inequality? This comparative ethnography of two African cities, Maputo and Johannesburg, presents a new narrative about social life in cities often described as sharply divided. Based on the ethnography of entangled lives unfolding in a township and in a suburb in Johannesburg, in a bairro and in an elite neighborhood in Maputo, the book includes case studies of relations between domestic workers and their employers, failed attempts by urban elites to close off their neighborhoods, and entanglements emerging in religious spaces and in shopping malls. Systematizing comparison as an experience-based method, the book makes an important contribution to urban anthropology, comparative urbanism and urban studies.